2007
DOI: 10.1113/expphysiol.2007.039677
|View full text |Cite
|
Sign up to set email alerts
|

The human genioglossus response to negative airway pressure: stimulus timing and route of delivery

Abstract: The genioglossus reflex response to sudden onset pulses of negative airway pressure (NAP) in humans is reported to occur more commonly at end rather than onset of expiration when delivered via a mouthpiece. We examined whether this response was modulated by the route of stimulus delivery throughout the respiratory cycle. The genioglossus surface EMG (GGsEMG) response to NAP delivered randomly throughout the respiratory cycle was measured in a set of experiments: (i) 40 stimuli of NAP at −5, −7.5 and −10 cmH 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…On the other hand, although anesthetized and decerebrate animal models allow access to all of the tongue muscles, the influence of drugs precludes the study of natural state changes on the respiratory drive to the motoneuron pool. Moreover, studies are typically done in tracheotomized animals, allowing airflow to bypass the upper airway, which greatly disturbs not only the natural function of the upper airway, but presumably the neural drive to the hypoglossal motoneuron pool (Berry et al, 2003; Chamberlin et al, 2007; Doherty et al, 2008; Eckert et al, 2007; Horner et al, 1991; Leiter and Daubenspeck, 1990; Malhotra et al, 2002; Mathew et al, 1982; van Lunteren et al, 1984). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, although anesthetized and decerebrate animal models allow access to all of the tongue muscles, the influence of drugs precludes the study of natural state changes on the respiratory drive to the motoneuron pool. Moreover, studies are typically done in tracheotomized animals, allowing airflow to bypass the upper airway, which greatly disturbs not only the natural function of the upper airway, but presumably the neural drive to the hypoglossal motoneuron pool (Berry et al, 2003; Chamberlin et al, 2007; Doherty et al, 2008; Eckert et al, 2007; Horner et al, 1991; Leiter and Daubenspeck, 1990; Malhotra et al, 2002; Mathew et al, 1982; van Lunteren et al, 1984). …”
Section: Introductionmentioning
confidence: 99%
“…Mid-inspiration Early expiration Mid-expiration Short latency excitation (<40 ms) 12/12 (100%) 11/12 (92%) 6/12 (50%) * 4/10 (40%) * , † Long latency excitation (>40 ms) 0/12 (0%) 1/12 (8%) 3/12 (25%) 6/10 (60%) * , † Suppression after excitation 3/12 (25%) 4/12 (33%) 1/12 (8%) 0/10 (0%) Suppression before excitation 0/12 (0%) 0/12 (0%) 1/12 (8%) 1/10 (10%) * Significant difference from early inspiration; † significant difference from mid-inspiration; P < 0.05. between inspiration and expiration (Doherty et al 2008). This suggests that the current findings either are specific to people with OSA or may relate to other differences in methodology.…”
Section: Early Inspirationmentioning
confidence: 72%
“…Earlier studies (Woodall et al 1989;Horner et al 1991;Wheatley & White, 1993;Tantucci et al 1998) have shown differences in the genioglossus reflex depending on the timing of the negative pressure with the most robust responses during end expiration and early inspiration. In contrast, a more recent study (Doherty et al 2008) showed no change in the genioglossus response to negative pressure delivered at different time points during the respiratory cycle.…”
Section: Introductionmentioning
confidence: 67%
“…Also, the route of breathing may affect the magnitude and/or pattern of muscle response to inspiratory obstruction: EMG:Pes measurements were performed with an external resistive load and a mouthpiece, and oral breathing has been shown to reduce the GG response to hypoxaemia (Tafil‐Klawe & Klawe, ). However, the GG‐EMG response to negative pressure in the upper airway is not affected by the route of application of the negative pressures (Doherty, Cullen, Nolan, & McNicholas, ).…”
Section: Discussionmentioning
confidence: 99%